On the Holder continuity of approximate solution mappings to parametric weak generalized Ky Fan inequality - Peng, Z.; Yang, X.; Teo, Kok Lay (American Institute of Mathematical Sciences, 2015)
In this paper, by using a scalarization method, we establish sufficient conditions for H older continuity of approximate solution mapping to a class of parametric weak generalized Ky Fan Inequality with set-valued mappings. These results extend and improve some known results in the literature. Furthermore, some examples are given to illustrate the obtained results.